Profile of Oral Health in Iran - T Malek Mohammadi; A Hajizamani (Tehran University of Medical Sciences, 2005)
Background: This paper is a review of current oral health in Iran Aim. The main aim of the review was to look at the current oral health profile of Iran from the dental public health point of view and to make comparison other countries. Methods: The review tried to consider all published papers and electronic information regarding the subject. Dental caries and periodontal disease rates, and dental health delivery services in Iran were explored. Some information was collected personally by e-mail or telephone contact with related people or organization. Results: About 15000 dentists (1/5000 population) are delivering oral health in private and community dental services. More than fifty percent of children age 12- year-old has some caries experience. Conclusion: There is not much difference between dental caries rate in Iran and other countries. However, the relevant studies in Iran are neither reliable nor carried out on a national basis. There is need for a nationwide survey of all aspects of oral health in Iran. Improving oral health should be considered as an important part of the public health programme in Iran.